Prostate-Specific Membrane Antigen (PSMA) Promotes Angiogenesis of Glioblastoma Through Interacting With ITGB4 and Regulating NF-κB Signaling Pathway - Gao, Yang; Zheng, Hui; Li, Liangdong; Feng, Mingtao; Chen, Xin; Hao, Bin; Lv, Zhongwei; Zhou, Xiaoyan; Cao, Yiqun (Frontiers in Cell and Developmental Biology, 2021)
Background: Glioblastoma multiforme (GBM) is the most common primary malignant tumor in the central nervous system (CNS), causing the extremely poor prognosis. Combining the role of angiogenesis in tumor progression and the role of prostate-specific membrane antigen (PSMA) in angiogenesis, this study aimed to explore the functions of PSMA in GBM. Methods: Clinical GBM specimens were collected from 60 patients who accepted surgical treatment in Fudan University Shanghai Cancer Center between January 2018 and June 2019. Immunohistochemical staining was used to detect PSMA and CD31 expression in GBM tissues. Prognostic significance of PSMA was evaluated by bioinformatics. Human umbilical vein endothelial cells (HUVECs) transfected with PSMA overexpression plasmids or cultured with conditioned medium collected based on GBM cells, were used for CCK8, Transwell and tube formation assays. High-throughput sequencing and immunoprecipitation were used to explore the underlying mechanism. Furthermore, the in vivo experiment had been also conducted. Results: we demonstrated that PSMA was abundantly expressed in endothelium of vessels of GBM tissues but not in vessels of normal tissues, which was significantly correlated with poor prognosis. Overexpression of PSMA promotes proliferation, invasion and tube formation ability of human umbilical vein endothelial cells (HUVECs). Moreover, U87 or U251 conditioned medium could upregulated PSMA expression and showed similar effects on phenotypes of HUVECs, all of which could be partially attenuated by 2-PMPA treatment. The mechanistic study revealed that PSMA might promote angiogenesis of GBM through interacting Integrin β4 (ITGB4) and activating NF-κB signaling pathway. The in vivo growth of GBM could be alleviated by the treatment of 2-PMPA. Conclusion: This study identified PSMA as a critical regulator in angiogenesis and progression of GBM, which may be a promising therapeutic target for GBM treatment.